2022
DOI: 10.1016/j.bbrc.2021.11.104
|View full text |Cite
|
Sign up to set email alerts
|

The positive feedback loop of NHE1-ERK phosphorylation mediated by BRAFV600E mutation contributes to tumorigenesis and development of glioblastoma

Abstract: The occurrence rate of v-raf murine sarcoma viral oncogene homolog B1 (BRAF) activating mutation V600E (BRAF V600E ) in glioblastoma multiforme (GBM) is more than 50%. Na/H exchanger 1 (NHE1), a main pH regulator affecting cell microenvironment, is hyper-expressed in GBM. However, the relationship between BRAF V600E signal pathway and NHE1 in GMB cells remains unclear. This study found that NHE1 was a downstream target of BRAF V600E and an upstream factor of extracellular signal-regulated kinase (ERK). In addi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…As for proliferation, it was found to be reduced in U87MG and T98G cells but elevated in DBTRG-05MG. Discrepancies for DBTRG-05MG might be attributed to the specific features of these cells (among four investigated cell lines), e.g., the presence of a BRAF V600E mutation [ 73 , 74 ]. It is known that this alteration can lead to the maintenance of proliferation, transformation, and tumorigenicity [ 75 ] and that multiple proliferation-related signaling pathways are simultaneously active when V600E is present [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…As for proliferation, it was found to be reduced in U87MG and T98G cells but elevated in DBTRG-05MG. Discrepancies for DBTRG-05MG might be attributed to the specific features of these cells (among four investigated cell lines), e.g., the presence of a BRAF V600E mutation [ 73 , 74 ]. It is known that this alteration can lead to the maintenance of proliferation, transformation, and tumorigenicity [ 75 ] and that multiple proliferation-related signaling pathways are simultaneously active when V600E is present [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gene mutations are a common tumorigenic mechanism in liver cancer ( 31 34 ). In this study, it was found that CLGN was rarely mutated in HCC patients, which suggests that the pathological effects of CLGN may not be exerted through genetic mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, NHE1 protein blockade promoted an immunogenic tumor microenvironment by inducing the accumulation of CD8 T cells, enhancing interferon-gamma (IFN-γ) expression, and rendering animals sensitive to anti-PD-1 treatment [66]. Another study demonstrated that NHE1 is an upstream factor of the extracellular signal-regulated kinase (ERK) and a downstream target of the BRAFV600E mutation, while a positive feedback loop between NHE1-ERK phosphorylation under the regulation of the BRAFV600E mutation seems to contribute to GB cell proliferation and invasion [67]. The proliferative and invasive properties of BRAFV600E-mutant and -wild-type GB cells were suppressed by an NHE1 and/or BRAFV600E inhibitor, with the combination of both resulting in more effective inhibition, suggesting a promising new therapeutic option for GB, especially when BRAF is mutated [67].…”
Section: Slc Implication In Glioma Proliferation and Progressionmentioning
confidence: 99%
“…Another study demonstrated that NHE1 is an upstream factor of the extracellular signal-regulated kinase (ERK) and a downstream target of the BRAFV600E mutation, while a positive feedback loop between NHE1-ERK phosphorylation under the regulation of the BRAFV600E mutation seems to contribute to GB cell proliferation and invasion [67]. The proliferative and invasive properties of BRAFV600E-mutant and -wild-type GB cells were suppressed by an NHE1 and/or BRAFV600E inhibitor, with the combination of both resulting in more effective inhibition, suggesting a promising new therapeutic option for GB, especially when BRAF is mutated [67]. Although the abovementioned findings show that NHE1 might be a novel treatment target against brain tumorigenesis and progression, there are no clinical studies to date evaluating the pharmacological inhibition of NHE1 protein in brain tumors [68].…”
Section: Slc Implication In Glioma Proliferation and Progressionmentioning
confidence: 99%